Emotion Regulation Strategies To Enhance Intelligence In Elementary School Children - Agustian Agustian; Listian Indriyani Achmad; Rini Sulistiyowati; Saiful Muktiali; Nenda Nenda; Djoko Nugroho (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2024)
Every child possesses unique characteristics shaped by various factors, such as self-reaction, developmental challenges, and environmental influences. Consequently, children often display a range of behaviors, including sadness, anger, aggression, and learning difficulties. This study focuses on the impact of emotional development on elementary school students. Employing a literature review approach, this research analyzes and interprets content from multiple sources. The findings emphasize the importance of addressing various aspects of elementary school children's lives, including their health, family dynamics, peer relationships, parental aspirations, as well as the guidance and educational approaches provided to them. Furthermore, emotional balance is considered crucial and can be achieved through environmental control and the development of skills to manage and respond to emotions in a balanced manner.